Intravenous iron to treat anaemia following critical care: a multicentre feasibility randomised trial. (February 2022) - Shah, Akshay; Chester-Jones, Mae; Dutton, Susan J.; Marian, Ioana R.; Barber, Vicki S.; Griffith, David M.; Singleton, Jo; Wray, Katherine; James, Tim; Drakesmith, Hal; Robbins, Peter A.; Frise, Matthew C.; et al.
Abstract: Background: Anaemia is common and associated with poor outcomes in survivors of critical illness. However, the optimal treatment strategy is unclear. Methods: We conducted a multicentre, feasibility RCT to compare either a single dose of ferric carboxymaltose 1000 mg i.v. or usual care in patients being discharged from the ICU with moderate or severe anaemia (haemoglobin ≤100 g L −1 ). We collected data on feasibility (recruitment, randomisation, follow-up), biological efficacy, and clinical outcomes. Results: Ninety-eight participants were randomly allocated (49 in each arm). The overall recruitment rate was 34% with 6.5 participants recruited on average per month. Forty-seven of 49 (96%) participants received the intervention. Patient-reported outcome measures were available for 79/93 (85%) survivors at 90 days. Intravenous iron resulted in a higher mean (standard deviation [sd ]) haemoglobin at 28 days (119.8 [13.3] vs 106.7 [14.9] g L −1 ) and 90 days (130.5 [15.1] vs 122.7 [17.3] g L −1 ), adjusted mean difference (10.98 g L −1 ; 95% confidence interval [CI], 4.96–17.01; P <0.001) over 90 days after randomisation. Infection rates were similar in both groups. Hospital readmissions at 90 days post-ICU discharge were lower in the i.v. iron group (7/40 vs 15/39; risk ratio=0.46; 95% CI, 0.21–0.99; P =0.037). The median (inter-quartile range) post-ICU hospital stay was shorter in the i.v. iron group but did not reach statistical significance (5.0 [3.0–13.0] vs 9.0 [5.0–16.0] days, P =0.15). Conclusion: A large, multicentre RCT of i.v. iron to treat anaemia in survivors of critical illness appears feasible and is necessary to determine the effects on patient-centred outcomes. Clinical trial registration: ISRCTN13721808 (www.isrctn.com ).